If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6y-12=-33
We simplify the equation to the form, which is simple to understand
-6y-12=-33
We move all terms containing y to the left and all other terms to the right.
-6y=-33+12
We simplify left and right side of the equation.
-6y=-21
We divide both sides of the equation by -6 to get y.
y=3.5
| -6y-13=-33 | | x^2-32x+135=0 | | -5b-6-10b-8= | | 0.06x=100 | | 12.4=n+2.8 | | 8[4(n-4)+18]-[3(2n-3)+3]= | | 13n+13= | | 13+13= | | 6+.10=.15+8 | | (24y^7)/(12y^3) | | (17-2*3)-15= | | 9v=5v+8 | | 4(X+7)=5(X+6) | | 2x+6=3x+3 | | 5(w+2)=w+6(w-3) | | 8y+2=3y-13 | | (15-5*2)-17= | | -56=-7(-2+n) | | 1/2(n-8)=26 | | 74m=100 | | 59=-3b+5 | | -63m+257=.74 | | -63m+257=100 | | 6/x+7/y | | (-3x+12)/4 | | 2(4p+10)=26 | | -63m+257=74m | | x(x+4)=x^2-12 | | 102=6s+12 | | 7x-3x-10=0 | | W/-5+17=-4 | | y=-7/9x+1 |